2002
DOI: 10.1001/archpsyc.59.9.825
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Neuropeptide Y Leu7Pro Polymorphism Associated With Alcohol Dependence in a Large Population Sample From the United States

Abstract: These results suggest that the NPY Pro7 allele is a risk factor for alcohol dependence. This is only the second specific genetic mechanism ever identified that modulates risk for alcohol dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
100
4
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(106 citation statements)
references
References 36 publications
0
100
4
2
Order By: Relevance
“…Several of the genes that are central to drug response and neuroadaptation have already been tested as leading candidates in genetic studies in humans. So far, the brain-derived neurotrophic factor (BDNF) 115 , the 5-hydroxytryptamine (serotonin) receptor 1B (HTR1B) 24 , the γ-aminobutyric acid receptor A (GABA A ) receptor 38 , neuropeptide Y (NPY) 116 , and the dopamine D2 receptor (DRD2) 117 genes have been implicated in animal studies and evaluated in humans, with promising results. However, most of the strong candidate genes to emerge from animal neurobiological studies of addiction have yet to be evaluated for sequence variation and linkage to human addictive behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the genes that are central to drug response and neuroadaptation have already been tested as leading candidates in genetic studies in humans. So far, the brain-derived neurotrophic factor (BDNF) 115 , the 5-hydroxytryptamine (serotonin) receptor 1B (HTR1B) 24 , the γ-aminobutyric acid receptor A (GABA A ) receptor 38 , neuropeptide Y (NPY) 116 , and the dopamine D2 receptor (DRD2) 117 genes have been implicated in animal studies and evaluated in humans, with promising results. However, most of the strong candidate genes to emerge from animal neurobiological studies of addiction have yet to be evaluated for sequence variation and linkage to human addictive behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The attributable fraction, which is the proportion of cases in the study population that would not have occurred had the risk factor (risk allele) not been present, is a useful measure to quantify the impact of the allele on the development of PTSD. [25] The analysis revealed that 14% of the susceptibility to PTSD could be attributed to having the CC genotype of the 957C4T DRD2 polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that these data add meaningfully to the existing findings in the study of the molecular genetics of alcoholism. Many genes, such as certain alcohol dehydrogenases and aldehyde dehydrogenase, 27 neuropeptide Y, 28 and GABA-A receptor, 29 have already been implicated in genetic risk for alcoholism. To our knowledge, this is the second fine-mapping report focusing on the genetic background of alcoholism using a positional strategy.…”
Section: Discussionmentioning
confidence: 99%